Analysing English Collocation Usage and Errors in Cambodian Students' Essay Writing: Insights and Implications - Vy Rany; Havid Ardi; Em Moeurn (STAI Hubbulwathan Duri, 2025)
English has become the dominant global language, and the accurate use of collocations is a key component of language proficiency. In Cambodia, the role of collocation knowledge in English writing remains underexplored. This qualitative study employed a descriptive design to examine grammatical collocation use among 13 Cambodian students through their essay writing. The primary aim was to identify both the types of grammatical collocations produced and the errors made in their usage. The analysis revealed that the most commonly used collocation type was Preposition + Noun, followed by Noun + Preposition. Less frequent patterns included Noun + To-infinitive and Adjective + Preposition, while Adjective + That-clause and Verb + Adverb were rarely found. In terms of accuracy, Preposition + Noun yielded the highest number of errors (12), followed by Noun + Preposition (5). Other types showed minimal or no errors. These findings highlight the students’ struggles with common collocation forms, particularly those involving prepositions. The most frequent source of error was interlingual transfer (88.45%), indicating influence from the native language. Other contributing factors included the learning environment (84.60%), intralingual transfer (53.80%), and communication strategies (50%). The study underscores the need for explicit instruction in collocation use, particularly in high-error patterns like Preposition + Noun. Addressing error sources such as native language interference can enhance students’ collocational competence in academic writing.